An Analytical Approach to Customer Sentiments using NLP Techniques and Building a Brand Recommender Based on Popularity Score - Baruah, Sudesna; Pal, Subhabaha (Indian Journal of Computer Science, 2019)
Natural language processing (NLP) is a subfield of linguistics, computer science, information engineering, and artificial intelligence that is concerned with the interactions between computers and human (natural) languages, in particular how to program computers to process and analyze large amounts of natural language data. This field has a great importance in many areas like retail stores and websites, social networking sites like Twitter, Facebook etc.; for understanding the various views or sentiments of the public or the consumers or end users, regarding a particular product or topic.